Reverse adipofascial radial forearm flap surgery for soft-tissue reconstruction of hand defects - Akdağ, Osman; Karameşe, Mehtap; Nebilselimoğlu, Muhammed; Akatekin, Ahmed; Abacı, Malik; Sütçü, Mustafa; Tosun, Zekeriya (My University, 2016)
Objective: The reverse radial forearm flap has been used for soft-tissue hand defect surgical procedures worldwide. One of the major drawbacks of this flap, however, is donor site morbidity, as the donor site is closed with a skin graft. Problems with skin graft donor areas include adhesion, contracture, and wound-healing complications. In this study, only the adipofascial component of a reverse radial forearm flap was used to prevent these problems; in addition, a skin graft was applied over the flap instead of over the donor site. Methods: Between January 2011 and December 2013, a total of 13 hand defects were reconstructed with a reverse adipofascial radial forearm flap. Patients were evaluated for functional results using total active motion criteria and disability of the arm, shoulder, and hand scores, operation time, hospitalization time, and patient satisfaction. Results: All flaps and grafts placed on flaps survived completely and donor sites healed without complications. The total active motion criteria and the disability of the arm, shoulder, and hand score demonstrated that the functional outcomes were successful. Patient satisfaction scores using the visual analog scale had a mean of 88.3 (SD = 2.95) mm. Operation time for the flap surgery was 126.1 (SD = 21.80) minutes, and patients were discharged at an average of 6.3 (SD = 1.44) days. Conclusion: Use of an adipofascial component in reverse radial forearm flap surgery is appropriate for reducing problems with donor site skin grafts. Patients’ functional outcomes denoted that the reverse adipofascial radial forearm flap is a reliable and effective method to cover soft-tissue defects of the hand.
Keywords: Reverse Adipofascial Radial Forearm Flap; Hand; Soft-Tissue Defect; Radial Forearm Flap; Donor-Site Morbidity